Economical synthesis of composites of FeNi alloy nanoparticles evenly dispersed in two-dimensional reduced graphene oxide as thin and effective electromagnetic wave absorbers. Issue 15 (23rd February 2018) - Li, Juan; Zhang, Dong; Qi, Hui; Wang, Guangming; Tang, Jimin; Tian, Ge; Liu, Anhua; Yue, Huijuan; Yu, Yang; Feng, Shouhua
Abstract : Two-dimensional magnetic FeNi/rGO composites with excellent microwave absorbing performance have been synthesized under the assistance of glucose. Abstract : Developing electromagnetic wave absorbing materials prepared by a facile and economical way is a great challenge. Herein, we report a feasible route to synthesize a series of two-dimensional FeNi/rGO composites by a hydrothermal method followed by a carbonization process. The characterization confirms that nano-sized FeNi alloy nanoparticles are evenly supported onto graphene sheets without aggregation. The homogeneous dispersion of the nanoparticles may result from the introduction of glucose and the oxygen-containing groups on the surface of the graphene oxide. Measurements show that the microwave attenuation capability of the composites can be improved dramatically by adjusting the proportion of dielectric and magnetic components. Consequently, the two-dimensional magnetic material (FeNi/rGO-100) exhibits an excellent microwave absorption performance. In detail, the minimum reflection loss of −42.6 dB and effective bandwidth of 4.0 GHz can be reached with a thinner thickness of 1.5 mm. This study demonstrates that synergistic effects among the magnetic particles, reduced graphene oxide and amorphous carbon layers give rise to the highlighted microwave attenuation ability. Overall, the FeNi/rGO composite is a promising candidate to be used as a microwave absorber, and the feasible and economical method has shown potential application to construct multitudinous two-dimensional materials.